Self-perception of youth overusing psychoactive substances - Makara-Studzińska, Marta; Trela, Jadwiga; Jankowska-Nowak, Renata; Sidor, Katarzyna (Polish Journal of Public Health, 2009)
Purpose. The study aims to determine the characteristic features of self-conception of youth overusing psychoactive substances.Material and method. The study comprised 100 people aged 14-19 overusing psychoactive substances. The control group consisted of 301 people not treated because of the risky behavior. There was H.G. Gough and Helibrun’s Adjectival Test (ACL) used in the study.Results. The youth overusing psychoactive substances used negative adjectives in self-description. Comparing to the control group it is characterized by the higher level of need for domination (Dom), need for turning the others attention to them (Exh), need for autonomy (Aut), it is excessively ambitious and impatient (Mas). Comparing to the youth from the control group, its need for self-understanding, understanding the others (Int) and taking care of the others is reduced (Nur). In the fi eld of self-control (S-Cn), personal adaptation (Pad), leader’s skills (Mls), youth from the tested group obtained lower results than the control group. In the fi eld of the perfect self-image youth from the tested group described themselves using positive adjectives in predominant number. Youth from the tested group, comparing to the control group, wants to have higher level of: need for achievements (Ach), aggression (Agg), taking care of the others (Nur), change (Cha), contacts with the opposite sex (Het), affi liation (Aff), support from the others (Suc), self-confi dence (S-Cfd) and autonomy (Aut).Conclusions. The obtained results confi rm the existence of relationship between behaviors risky for health and life and negative self-image resulting from low self-confi dence and divergence between “real myself” and inadequate to own possibilities “perfect myself”.